Renal failure caused by a partly calcified aortic aneurysm in a patient with dabigatran therapy: A case report. Issue 17 (April 2017) - Jud, Philipp; Gary, Thomas; Tiesenhausen, Kurt; Portugaller, Rupert; Hackl, Gerald; Brodmann, Marianne
Abstract: Rationale: Abdominal aortic aneurysms (AAAs) are mostly asymptomatic. If aortic aneurysms become symptomatic, complications include peripheral embolization, acute aortic occlusion, and aortic rupture. However, there are also unusual complications caused by aortic aneurysms. Patient concerns: An 87-old male with dabigatran therapy presented with newly developed melena and acute renal failure. Radiological imaging revealed an AAA with thrombotic and calcified deposits which affected the renal arteries. Diagnoses: Gastrointestinal bleeding and hypercoagulation caused by renal failure which was triggered in turn due to an AAA. Interventions: Adapted antihypertensive therapy and initiation of simvastatin 40mg once daily as well as antiplatelet therapy with aspirin 50 mg once daily due to patient's refusal of any aneurysm intervention. Outcome: Neither bleeding event nor aneurysm rupture occurred with the adapted antihypertensive therapy, simvastatin and aspirin. Lessons: Nonruptured AAAs can cause rare, unusual, and even life-threatening complications depending on their size and anatomical position.